Machine Learning Does Not Improve Humeral Torsion Prediction Compared to Regression in Baseball Pitchers - Garrett S Bullock; Charles A Thigpen; Gary S Collins; Nigel K Arden; Thomas K Noonan; Michael J Kissenberth; Ellen Shanley (International Journal of Sports Physical Therapy)
# Background